MORTALITY RATES AND YIELD PER RECRUIT IN NEMIPTERUS JAPONICUS (BLOCK) - Krishnamurthy, B (Indian Journal of Fisheries, 2011)
Both the yield per recruit in Weight ( Y ^ / R ) and in numbers (Yj^/R) in Nemipterus japonicus (Bloch) increase with increased fishing mortality i.e., with increased fishing mortality, yield increases to an asymptote. Since the rate of exploitation works to about 3% only, it seems reasonable to remark that the stocks of N. japonicus are very much underexploited